Kejadian Stunting terhadap Pola Pemberian Makan pada Balita Usia 12-59 Bulan di Wilayah Kerja Puskesmas Lobu, Kabupaten Banggai - Ramona Tepi; Ma’rifat Istiqa Mukty (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Stunting is a form of malnutrition characterized by height-for-age indicators. The height-for-age (H/A) indicator reflects chronic nutritional issues resulting from prolonged adverse conditions. The aim of this study is to identify the factors influencing the incidence of stunting in children aged 12–59 months in the working area of the Lobu Health Center, Banggai Regency. This research employs a quantitative approach with a cross-sectional study design. The population in this study consists of mothers with stunted children. A total of 85 respondents were selected as the sample using a total sampling technique. The independent variables in this study are maternal education level, family income, and feeding practices. The dependent variable is stunting. Data collection was conducted using questionnaires, and children's height was measured with a microtoise and converted into standard z-scores. The results indicate a significant effect of feeding practices on the incidence of stunting in children aged 12-59 months (p=0.002; r=0.326). Improved feeding practices are associated with a reduction in stunting rates in the working area of the Lobu Health Center, Banggai Regency, emphasizing the need to enhance feeding practices. Therefore, nurses and other healthcare professionals should intensify health promotion efforts regarding proper feeding practices for young children.